SISTEM MONITORING SUHU DAN KELEMBAPAN BERLEBIH DI RUANGAN LABORATORIUM KOMPUTER BERBASIS IOT MENGGUNAKAN ESP32 DAN DHT22 - TRI MERI WULANDARI; Nur Azizah; Firman Jaya (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Computer laboratories require stable temperature and humidity conditions for optimal device function and to avoid the risk of damage due to overheating or extreme humidity. However, available monitoring systems generally only display environmental data without an automatic early warning mechanism when parameters exceed safe limits. This condition has the potential to cause delays in handling, decreased device performance, increased maintenance costs, and disruption to operational activities. This study aims to design and implement an Internet of Things (IoT)-based temperature and humidity monitoring system equipped with an early warning feature. The research method used is Research and Development (R&D) with the Borg & Gall model, which includes the stages of problem identification, data collection, system design, testing, and evaluation. The system was developed using an ESP32 microcontroller and a DHT22 sensor to read temperature and humidity, with data displayed in real time through the Blynk application. In addition, the system is integrated with Telegram to send automatic notifications when environmental conditions are outside safe limits. Test results show that the system is capable of continuous monitoring and sending early warning notifications effectively. Thus, the developed system has the potential to be an effective monitoring and early warning solution to support computer laboratory environmental management.